Quand les entreprises agroalimentaires « végétalisent » leur offre - Amélie Aubert-Plard; Titouan Bénégui (Communiquer)
Faced with the societal issue of ecological and food transition, this article seeks to understand to what extent citizens perceive these agri-food companies as actors of change, and the consumption of their new plant-based alternatives as a way to participate in. Our study was led by a qualitative field survey conducted during the year 2021 in the urban area of Île-de-France, and by mobilizing theories of environmental communication and the socio-anthropology of food. The first result presented in this article is a typology on the citizens’ attitudes towards this societal issue. This typology allows us to deduce two main levers of commitment for citizens toward this issue which are the awareness obtained by a personal empirical experience and the transmission of informations within the interpersonal network. It also reveals that according to their level of commitment towards the societal issue of food transition, citizens don’t have the same reaction to agrifood companies’ offers and communication. Finally, the article questions the relevance of the industrial plant-based offer and the associated discourse taking into account the everyday concerns of citizens, in terms of transparency and information.